2001
DOI: 10.1176/appi.ajp.158.7.1052
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Analysis of the Association Between the 7-Repeat Allele of the Dopamine D4 Receptor Gene and Attention Deficit Hyperactivity Disorder

Abstract: Although the association between ADHD and DRD4 is small, these results suggest that it is real. Further studies are needed to clarify what variant of DRD4 (or some nearby gene) accounts for this association.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
429
2
21

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 682 publications
(465 citation statements)
references
References 28 publications
13
429
2
21
Order By: Relevance
“…Further studies on chronically ill schizophrenia patients, aimed at quantitative assessments of specific cognitive functions and social functioning, are needed to adequately evaluate D 4 receptor as a potentially important therapeutic target. Genetic studies have strongly implicated D 4 receptor polymorphism in ADHD (La Hoste et al, 1996;Faraone et al, 2001). Using young rats with neonatal 6-hydroxydopamine lesions as a model for ADHD, we reported that locomotor hyperactivity in this model was inhibited by several selective D 4 antagonists as by the stimulant methylphenidate, but not antagonists that bind preferentially to the D 2 or 5-HT 2A receptor Zhang et al, 2001Zhang et al, , 2002.…”
Section: Discussionmentioning
confidence: 74%
“…Further studies on chronically ill schizophrenia patients, aimed at quantitative assessments of specific cognitive functions and social functioning, are needed to adequately evaluate D 4 receptor as a potentially important therapeutic target. Genetic studies have strongly implicated D 4 receptor polymorphism in ADHD (La Hoste et al, 1996;Faraone et al, 2001). Using young rats with neonatal 6-hydroxydopamine lesions as a model for ADHD, we reported that locomotor hyperactivity in this model was inhibited by several selective D 4 antagonists as by the stimulant methylphenidate, but not antagonists that bind preferentially to the D 2 or 5-HT 2A receptor Zhang et al, 2001Zhang et al, , 2002.…”
Section: Discussionmentioning
confidence: 74%
“…This strategy has proven to be informative in the case of the 7-repeat DRD4 variant. Faraone et al (2001) concluded that in a meta-analysis of 22 studies, a small but highly significant association exists at DRD4. Future directions for molecular genetic studies in ADHD include increasing sample size and power by collaboration, coordinating usage of data collection instruments to allow for comparison between research groups, the use of meta-analysis, and a move toward better characterization of the ADHD phenotype.…”
Section: Integrating Our Results With Existing Workmentioning
confidence: 99%
“…To date, there have been 16 studies examining for association between the 7 repeat DRD4 polymorphism and ADHD, with positive results in many (LaHoste et al 1996;Swanson et al 1998b;Smalley et al 1998;Rowe et al 1998;Faraone et al 1999;Muglia et al 2000;Holmes et al 2000;Sunohara et al 2000;Tahir et al 2000a;Mill et al 2001), but not all (Castellanos et al 1998; Comings et al 1999;Eisenberg et al 2000;Hawi et al 2000a;Kotler et al 2000;Todd et al 2001) studies. A recent meta-analysis of DRD4 by Faraone et al 2001 supported an overall association (albeit small) between DRD4 and ADHD. Case-control studies were more strongly significant (OR ϭ 1.9, p ϭ .00000008) than familybased studies (OR ϭ 1.4, p ϭ .02).…”
mentioning
confidence: 98%
“…[4][5][6][7][8] Various genetic studies using this polymorphism have implicated a seven-repeat allele in behavioral disorders, as for example, in novelty-seeking behavior and attention deficit hyperactivity disorder (ADHD). [9][10][11] The three most common polymorphic variants of the receptor, D4.2, D4.4 and D4.7, are functionally and pharmacologically nearly indistinguishable from each other. 6,8,12,13 However, mice deficient in D4 expression display increased anxiety 14 and altered exploratory behavior.…”
Section: Introductionmentioning
confidence: 99%
“…4 This particular variant is also associated in various studies with ADHD. [9][10][11] To date, only a limited number of studies have addressed whether the different variants can differentially modulate receptor function. The different receptor variants show no major differences in pharmacology.…”
Section: Introductionmentioning
confidence: 99%